Paradigma Thomas Kuhn : Revolusi Ilmiah dan Penerapan dalam Bimbingan Konseling - Pristiwanti, Yuwanita (JURNAL KONSELING GUSJIGANG, 2023)
A paradigm is referred to as what we will obtain from examining the behavior of members of a scientific community that has been previously determined and used as a constellation of beliefs, values, techniques, etc. that have been carried out by members of that scientific community. recognized community. This research aims to complement previous research, this research focuses on discussion, namely research that examines "Thomas S Kuhn's Thoughts on the Scientific Revolution and Its Application in Guidance Counselling".The method in this research discusses important and interesting issues reviewing Thomas S Kuhn's thoughts regarding the scientific revolution in science and how these thoughts can be applied in Guidance Counseling. With developments in research, ethics and societal needs, paradigms can experience significant shifts resulting in a revolution in guidance and counseling thinking. This allows the adaptation of new methods and approaches according to the complexity of the client's needs.